Hysteretic sediment fluxes in rainfall‐driven soil erosion: Particle size effects. Issue 11 (12th November 2016) - Cheraghi, Mohsen; Jomaa, Seifeddine; Sander, Graham C.; Barry, D. A.
Abstract: A detailed laboratory study was conducted to examine the effects of particle size on hysteretic sediment transport under time‐varying rainfall. A rainfall pattern composed of seven sequential stepwise varying rainfall intensities (30, 37.5, 45, 60, 45, 37.5, and 30 mm h −1 ), each of 20 min duration, was applied to a 5 m × 2 m soil erosion flume. The soil in the flume was initially dried, ploughed to a depth of 20 cm and had a mechanically smoothed surface. Flow rates and sediment concentration data for seven particle size classes (<2, 2–20, 20–50, 50–100, 100–315, 315–1000, and >1000 µm) were measured in the flume effluent. Clockwise hysteresis loops in the sediment concentration versus discharge curves were measured for the total eroded soil and the finer particle sizes (<2, 2–20, and 20–50 µm). However, for particle sizes greater than 50 µm, hysteresis effects decreased and suspended concentrations tended to vary linearly with discharge. The Hairsine and Rose (HR) soil erosion model agreed well with the experimental data for the total eroded soil and for the finer particle size classes (up to 50 µm). For the larger particle size classes, the model provided reasonable qualitative agreement with the measurements although the fit was poor for the largest size class (>1000 µm). Overall, it is found that hysteresis varies amongst particle sizes and that the predictions of the HR model are consistent with hysteretic behavior of different sediment size classes. Key Points: Hysteresis is attenuated with increasing sediment size The Hairsine and Rose soil erosion model reproduce hysteresis patterns Hysteresis is a manifestation of the changing composition of the surface layer